The true prognosis of resected distal cholangiocarcinoma. Issue 5 (18th January 2016) - Courtin‐Tanguy, Laetitia; Rayar, Michel; Bergeat, Damien; Merdrignac, Aude; Harnoy, Yann; Boudjema, Karim; Meunier, Bernard; Sulpice, Laurent
Abstract : Background: Prognosis of distal cholangiocarcinoma (DCC) after pancreaticoduodenectomy (PD) remains poorly assessed. The aims of this study were to describe the oncological results of PD in DCC and to compare its prognosis to pancreatic ductal adenocarcinoma (PDAC). Methods: All PD for periampullary carcinoma performed between January 2000 and March 2013 were extracted from a prospective database. Risk factors likely to influence overall (OS) and disease‐free (DFS) survivals of DCC were assessed by multivariable analyses. The DCC and PDAC prognoses were compared after matching using propensity score (nearest neighbor matching). Results: Of the 290 patients analyzed, 56 had DCC, with a mean age of 65 ± 15 years. The median OS was 36.9 months. Recurrence occurred in 35 patients (67%), mostly in the liver (37%). The median DFS was 14.6 months. Combined organ resection was an independent risk factor for worse OS and DFS ( P  = 0.01 and P  = 0.001, respectively). Matching analysis found no significant difference between DCC and PDAC in terms of OS ( P  = 0.284) or DFS ( P  = 0.438). Conclusion: This first propensity analysis demonstrated that DCC and PDAC have the same prognosis, linked to the high rate of early recurrence, particularly associated with the need for combined organ resection. J. Surg. Oncol. 2016;113:575–580 . © 2016 Wiley Periodicals, Inc.